Sodomy and the pirate tradition : English sea rovers in the seventeenth-century Caribbean - Burg, B. R. (Barry Richard), 1938- (Book collections on Project MUSE., 1995)
Pirates are among the most heavily romanticized and fabled characters in history. From Bluebeard to Captain Hook, they have been the subject of countless movies, books, children's tales, even a world-famous amusement park ride. In Sodomy and the Pirate Tradition, historian B.R. Burg investigates the social and sexual world of these sea rovers, a tightly bound brotherhood of men engaged in almost constant warfare. What, he asks, did these men, often on the high seas for years at a time, do for sexual fulfillment? Buccaneer sexuality differed widely from that of other all- male institutions such as prisons, for it existed not within a regimented structure of rule, regulations, and oppressive supervision, but instead operated in a society in which widespread toleration of homosexuality was the norm and conditions encouraged its practice. In his new introduction, Burg discusses the initial response to the book when it was published in 1983 and how our perspectives on all-male societies have since changed.